HIJACKING OF STATE POWER ON RELIGIOUS FREEDOM BY COMMUNITY ORGANIZATIONS IN INDONESIA - Prianto, Andi Luhur; Karimullah, Suud Sarim; Idri, Idri; Ibrahim, Zumiyati Sanu; Nugraha, Aat Ruchiat; Gönan, Yavuz (Universitas Islam Negeri Ar-Raniry, 2024)
This study aims to reveal the failure of the state to use its authority to ensure the fulfilment of religious freedom for all its citizens maximally and adequately because, in practice, the state sometimes takes refuge behind the slogan of neutrality when it sees the majority group committing violent practices against minority groups. This study uses a discourse analysis method with a phenomenological approach to understanding the meaning of various events and human interactions. Meanwhile, the data was collected through literature study, media study, and observation using content analysis and discourse analysis methods in processing the data. Then this research results in the finding that opening the state accommodation gap to the demands of the majority religious group will provide space for them to take advantage of the similarities in their religious ideology with state actors and then attempt to dictate state policy. The inability of the state to be neutral in solving the problems of its people, at the same time, has given rise to the impression that a handful of certain social classes have controlled the state. Even this research results also show that tendencies of intolerance and discrimination arise in the community.